- #1

- 699

- 5

2.2.2 [tex]3u_x+4u_y-2u=1\Rightarrow \omega_{\xi}+k\omega=\varphi(\xi,\eta)[/tex]

[tex]u(x,y)=u(\xi\cos{\alpha}-\eta\sin{\alpha},\xi\sin{\alpha}+\eta\cos{\alpha})=\omega(\xi,\eta)[/tex]

[tex]u_x=\omega_{\xi}\cos{\alpha}-\omega_{\eta}\sin{\alpha}[/tex]

[tex]u_y=\omega_{\xi}\sin{\alpha}+\omega_{\eta}\cos{\alpha}[/tex]

[tex]3(\omega_{\xi}\cos{\alpha}-\omega_{\eta}\sin{\alpha})+4(\omega_{\xi}\sin{\alpha}+\omega_{\eta}\cos{\alpha})-2w=1[/tex]

[tex]\omega_{\xi}(3\cos{\alpha}+4\sin{\alpha})+\omega_{\eta}(4\cos{\alpha}-3\sin{\alpha})-2\omega=1[/tex]

[tex]\displaystyle 4\cos{\alpha}-3\sin{\alpha}=0\Rightarrow \tan{\alpha}=\frac{4}{3}[/tex]

We have a 3,4,5 right triangle.

[tex]\displaystyle\cos{\alpha}=\frac{3}{5} \ \mbox{and} \ \sin{\alpha}=\frac{4}{5}[/tex]

Substitution:

[tex]\displaystyle \omega_{\xi}\left(3\frac{3}{5}+4\frac{4}{5}\right)+\omega_{\eta}(0)-2\omega=1[/tex]

[tex]\displaystyle \omega_{\xi}\left(\frac{9+16}{5}\right)-2\omega=1\Rightarrow\omega_{\xi}-\frac{2}{5}\omega=1[/tex]

I understand everything posted above; however, I don't understanding anything below.

Let

2.2.8 [tex]x=A\xi+B\eta \ \mbox{and} \ y=C\xi+D\eta[/tex]

A,B,C,D are constants to be determined, and set [tex]u(x,y)=\omega(\xi,\eta)[/tex] 2.2.9

Then, from [tex]\displaystyle\frac{\partial\omega}{\partial\xi}=u_x\frac{\partial x}{\partial\xi}+u_y\frac{\partial y}{\partial\xi}[/tex] and 2.2.8, 2.2.9, we see that with the choice A = 3, C = 4, Equation 2.2.2 becomes [tex]\omega_{\xi}-2\omega=1[/tex](nope don't see it).

[tex]u(x,y)=u(\xi\cos{\alpha}-\eta\sin{\alpha},\xi\sin{\alpha}+\eta\cos{\alpha})=\omega(\xi,\eta)[/tex]

[tex]u_x=\omega_{\xi}\cos{\alpha}-\omega_{\eta}\sin{\alpha}[/tex]

[tex]u_y=\omega_{\xi}\sin{\alpha}+\omega_{\eta}\cos{\alpha}[/tex]

[tex]3(\omega_{\xi}\cos{\alpha}-\omega_{\eta}\sin{\alpha})+4(\omega_{\xi}\sin{\alpha}+\omega_{\eta}\cos{\alpha})-2w=1[/tex]

[tex]\omega_{\xi}(3\cos{\alpha}+4\sin{\alpha})+\omega_{\eta}(4\cos{\alpha}-3\sin{\alpha})-2\omega=1[/tex]

[tex]\displaystyle 4\cos{\alpha}-3\sin{\alpha}=0\Rightarrow \tan{\alpha}=\frac{4}{3}[/tex]

We have a 3,4,5 right triangle.

[tex]\displaystyle\cos{\alpha}=\frac{3}{5} \ \mbox{and} \ \sin{\alpha}=\frac{4}{5}[/tex]

Substitution:

[tex]\displaystyle \omega_{\xi}\left(3\frac{3}{5}+4\frac{4}{5}\right)+\omega_{\eta}(0)-2\omega=1[/tex]

[tex]\displaystyle \omega_{\xi}\left(\frac{9+16}{5}\right)-2\omega=1\Rightarrow\omega_{\xi}-\frac{2}{5}\omega=1[/tex]

I understand everything posted above; however, I don't understanding anything below.

Let

2.2.8 [tex]x=A\xi+B\eta \ \mbox{and} \ y=C\xi+D\eta[/tex]

A,B,C,D are constants to be determined, and set [tex]u(x,y)=\omega(\xi,\eta)[/tex] 2.2.9

Then, from [tex]\displaystyle\frac{\partial\omega}{\partial\xi}=u_x\frac{\partial x}{\partial\xi}+u_y\frac{\partial y}{\partial\xi}[/tex] and 2.2.8, 2.2.9, we see that with the choice A = 3, C = 4, Equation 2.2.2 becomes [tex]\omega_{\xi}-2\omega=1[/tex](nope don't see it).

Last edited by a moderator: